2016
DOI: 10.1177/1557988315625775
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Influence of Nutrition Determinants on Construction Workers’ Food Choices

Abstract: Nutritional knowledge as well as economic, social, biological, and cultural factors have been known to determine an individual's food choices. Despite the existence of research on the factors which influence nutrition globally, there is little known about the extent to which these factors influence the food choices of construction workers, which in turn influence their health and safety during construction activities. The present article investigates the extent to which construction workers' nutrition is influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 42 publications
0
21
2
1
Order By: Relevance
“…Previous research has found connections between masculinity and poor health and lifestyle within the construction industry (Stergiou‐Kita et al, ), for example, relating to diet (McGlone & Baker, ; Okoro, Musonda, & Agumba, ) and mental health (Milner, Witt, Burnside, Wilson, & LaMontagne, ). Given that ‘males in the construction industry are at greater risk of suicide than those in the general working population’ (Milner et al, , p. 1), some of the health outcomes can be extremely serious.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found connections between masculinity and poor health and lifestyle within the construction industry (Stergiou‐Kita et al, ), for example, relating to diet (McGlone & Baker, ; Okoro, Musonda, & Agumba, ) and mental health (Milner, Witt, Burnside, Wilson, & LaMontagne, ). Given that ‘males in the construction industry are at greater risk of suicide than those in the general working population’ (Milner et al, , p. 1), some of the health outcomes can be extremely serious.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the results presented here have been presented in previous studies by the authors. 14,29 However, the current paper focuses on the validity and reliability of the research instrument developed and presents additional data that were useful in improving and refining the scale.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Other studies have had a broad scope and employed qualitative methods 12,13 and, more recently, a relationship between nutrition determinants and particular choices of food among construction workers was explored in South Africa. 14 Further, validated models of food-choice motives exist. [15][16][17][18][19] However, the factor structures evinced in these studies do not necessarily cater for or reflect the most important factors in other cultures and might have different connotations across different populations and cultures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations